Integrating theory and practice by self-directed inquiry-based learning? A pilot study. (December 2013) - Sjödahl Hammarlund, Catharina; Nordmark, Eva; Gummesson, Christina
Abstract Inquiry-based learning (IBL) is a research-based model promoting self-directed learning. The aim was to describe how five physiotherapists experienced their learning during their participation in two inquiry-based online courses. Primary data was their written self-reflections. Triangulation was done based on the self-reflections and the free text comments from three course evaluation surveys. Data analyses were done by qualitative content analysis. Autonomy emerged as the main theme, which was structured into three categories: (i) learning processes; (ii) perceiving increased self-efficacy; and (iii) transfer and implementation of theories and skills to practice. Being able to choose the research topic according to professional interest increased motivation and perceived meaning. Interacting with peers brought new perspectives and deeper understanding. The data triangulation revealed partially new aspects. Retrospectively, the participants expressed having gained new skills, which was augmented by their perception of professional relevance and the integration of theory in the clinical practice. Expressions of increased self-efficacy and the transfer of knowledge, understanding and skills to clinical practice, was interpreted as important parts of autonomy. In conclusion, courses with a research-based design may promote motivation and self-efficacy. Forum for peer support and collaboration was perceived to augment the creativity and broaden the understanding.